Jurusan Ilmu Sosiatri: "Hidup" Tak Banyak Orang Tahu, "Mati" Jangan Dulu - - Susetiawan (Jurnal Ilmu Sosial dan Ilmu Politik, 2005)
The origin and the exsistence of Jurusan Ilrnu Sosiatri have been discussed and produce various interpretation. The issues mostly deal with the status of pribumi and European-based science. Among these, some believe that Sosiatri is a specific Indonesian science. This article explains the history, contribution and the new agenda of Jurusan Ilnru Sosiatri in order to portray the development of Sosiatri.